2011
DOI: 10.1038/nrcardio.2010.224
|View full text |Cite
|
Sign up to set email alerts
|

Patent foramen ovale: anatomy, outcomes, and closure

Abstract: Patent foramen ovale (PFO) is a normal fetal communication between the right and left atria that persists after birth. PFO is a common finding that occurs in 20-34% of the population, although its prevalence decreases with age. In most cases, a PFO poses no threat to health. However, some PFOs have the ability to open widely under certain hemodynamic conditions, which enables any bloodborne material, such as thrombi, air, or vasoactive substances, to pass from the venous to the arterial circulation, with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
114
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 115 publications
2
114
0
11
Order By: Relevance
“…The septum secundum does not close fully and an oval-shaped opening remains, which becomes the foramen ovale. 17 Prior to birth, the fetus is dependent on the maternal circulation for oxygenation, as the immature fetal lungs do not yet participate in oxygen exchange. As such, the foramen ovale (as well as the ductus arteriosus), enables shunting of blood away from the pulmonary circulation.…”
mentioning
confidence: 99%
“…The septum secundum does not close fully and an oval-shaped opening remains, which becomes the foramen ovale. 17 Prior to birth, the fetus is dependent on the maternal circulation for oxygenation, as the immature fetal lungs do not yet participate in oxygen exchange. As such, the foramen ovale (as well as the ductus arteriosus), enables shunting of blood away from the pulmonary circulation.…”
mentioning
confidence: 99%
“…With the use of ventilation perfusion scanning, 1 study showed asymptomatic pulmonary emboli inUp to 25% of the population may have a PFO detectable on autopsy, with persistence after the birth of a connection between the right and left atria. 10,11 In patients with elevated right-sided pressures, flow through a PFO provides a mechanism of blood flow from the right heart to the left-sided circulation. In patients with a PFO, endovascular leads may pose a unique hazard, because the thrombi that develop on leads may shunt across the PFO to the systemic circulation, resulting in ischemic cerebrovascular events or other systemic thromboembolisms.…”
mentioning
confidence: 99%
“…It was also underlined an increased incidence of atrial fibrillation in the group of patients treated with closure device compared to the group in medical therapy (5.7% vs 0.7%, respectively, P <0.001). This aspect, according to some authors may have contributed, in the percutaneous treatment group, to the finding of a stroke rate higher than expected [25]. Therefore, the presentation of the results of CLOSURE I indicates that PFO closure with Starflex ® device does not significantly reduces the rate of recurrent events compared to medical therapy, at a 2 years follow-up.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the presentation of the results of CLOSURE I indicates that PFO closure with Starflex ® device does not significantly reduces the rate of recurrent events compared to medical therapy, at a 2 years follow-up. However, several criticisms have been raised [25]. Several methodological reasons, in fact, may explain why the end points were not reached: a follow-up too short to demonstrate the benefits of PFO closure and to overcome the procedural complications; the imprecision of the inclusion criteria, stroke or cryptogenic TIA.…”
Section: Discussionmentioning
confidence: 99%